Effect of soybean meal fermented with Bacillus subtilis BS12 on growth performance and small intestinal immune status of piglets - Yu Zhang (Taylor & Francis Group, 2018)
This study was aimed to screen a high-efficient strain for degrading antigenic protein in soybean meal (SBM) and evaluate the effect of fermented soybean meal (FSBM) on growth performance of piglets. A Bacillus subtilis strain BS12 was selected through plate and fermentation experiment, which reduced 92.36% less glycinin and 88.44% less β-conglycinin in SBM. A total of 192 piglets were assigned to receive either a diet of SBM with antibiotics (the control group) or a diet containing 10% FSBM without antibiotics. The average daily gain and feed intake of pigs fed FSBM were superior (p < .10) to those fed the control diet. Reduced (p < .05) mRNA expression of pro-inflammatory cytokines was detected in the jejunum and ileum of pigs fed FSBM. These results demonstrated that a diet containing BS12 FSBM improved growth performance by reducing dietary inflammation in piglets.